EDUCATION AND SPORT: THE VASCO GAMAS' SCHOOL (Fiep Bulletin - online, 2014)
This article has for objective to analyze the relationship between education and sport. For so much, he/she will make an exhibition of the characteristics of the school Vasco of Gama. The school Vasco of Gama is a regular school that works inside of the dependences of the Club of Regatas Vasco of Gama and it is offered exclusively for the sportsmen of this club. One of their characteristics is the adaptation of the schedules and calendar the needs of the sport teams of the club. For besides, expected sociability relationships in school atmosphere are differentiated at this school once all of the children are sportsmen of Gama's Vasco. Starting from this we can consider that aspects identity is more related to modalities than to clubs (all belong to the same club); the existence just of two girls it transforms the school universe in extremely macho; finally, in spite of just to exist to four years is noticed that the school is extremely sensitive the situation of the club, in other words, if the club this well, with success, this scenery contemplates a calm academic year and without larger problems in the school, if the club goes by difficulties the school also reflects these difficulties in their students' income. The school Vasco of Gama offers a rich place to think the existent relationship between education and sport.
Keywords: education; sport; soccer